SUPPLY CHAIN RISK ANALYSIS AND ASSESSMENT USING ANALYTICAL HIERARCHY PROCESS (AHP): A REVIEW - Victor Yuardi Risonarta; Arie Cahya Kamila (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
In these days, increasing consumer demand uncertainties, e.g. due to war in Europe, severe drought in west Europe or Covid pandemic, increase challenge in supply chain operation. Uncertainty and unreliable events interfere supply chain’s operations and strategies. As a result, increasing risks in supply chain becomes vulnerable and leads to undesired circumstance. A systematic approach is therefeore required to manage the risks. Of many methods, supply chain risk management (SCRM), as a part of supply chain management (SCM), is offered in this paper to address this challenge. The SCRM increases supply chain resilience agains many uncertainties. An important key of SCRM is risk assessment as risk-impact ordering method which can deliver solution with the lowest risks. Of many methods applied for risk assessment, analytic hierarchy process (AHP) provides several advantages, e.g. it can be used as multi-criteria decision making, it can be used with high flexibility and it can be used as subjective assessment. This paper discusses the AHP method in supply chain risk assessment as well as offers a new AHP structure applied for risk analysis.